Analisis Kerentanan Mata Pencaharian Masyarakat Pesisir Teluk Depapre, Jayapura, Papua - Yunus Pajanjan Paulangan; Muh. Arsyad Al Amin; Barnabas Barapadang; Yudi Wahyudin; Taryono Taryono (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2020)
Understanding the vulnerability of livelihoods is very important in identifying and developing alternative livelihoods for communities to achieve their welfare. Alternative livelihoods are intended so that people do not depend their livelihoods entirely on the use of natural resources. Thus, the exploitation pressure on natural resources, especially the coast and the sea can be minimized. The purpose of this study is to analyze the level of livelihood vulnerability of the people in Depapre Bay using the Livelihood Vulnerability Matrix method. The results of the analysis showed that the level of vulnerability of people's livelihoods is in the vulnerable category (2.44), where the variable value is still low in terms of disaster disruption, social networks, savings, means of production, production costs, and fulfillment of basic needs.Keywords: Vulnerability; Livelihood; Coastal Community; Exploitation Pressure; Natural Resources; Teluk Depapre; Papua